Using GPS and Self-Report Data to Examine the Relationship Between Community Mobility and Community Participation Among Autistic Young Adults. - Brusilovskiy, Eugene; Salzer, Mark S.; Pomponio Davidson, Amber; Feeley, Cecilia; Pfeiffer, Beth (American Journal of Occupational Therapy)
Importance: Community participation of autistic adults is important for health and well-being. Many clinical efforts and interventions aim to enhance community participation in this population. Objective: To empirically examine the relationship between community participation and community mobility. Design: A randomized controlled trial using data from baseline and 4- to 6-wk follow-up. Setting: Community organizations serving autistic adults in Philadelphia. Participants: Sixty-three autistic young adults with data on community mobility and participation from a prior study on public transportation use. Outcomes and Measures: Participants were tracked with GPS-enabled cell phones over a 2-wk period. A spatiotemporal data mining algorithm was used to compute the total number of destinations, nonhome destinations, unique destinations, percentage of time spent outside the home, and median daily activity space area from the GPS data. The Temple University Community Participation measure was used to collect self-report data in 21 different areas, and total amount, breadth, and sufficiency of participation were calculated. Results: Moderate and statistically significant associations were found between community mobility and participation variables at baseline and follow-up. However, changes in community mobility were not related to changes in community participation. Conclusion: Health policymakers and providers should consider community mobility as a factor that can affect community participation in autistic individuals. Plain-Language Summary: Lower levels of community participation among autistic young adults affect health outcomes and overall quality of life. Community mobility is often a barrier to community participation. An understanding of the relationship between community mobility and community participation can lead to occupational therapists tailoring specific interventions and policies that support autistic young adults to engage in important life activities within the community. Occupational therapists can tailor specific interventions and policies that support autistic young adults to engage in important life activities within the community.